Proportional concessions and the leximin solution - Driesen, Bram (Economics letters, 2012)
In this note we introduce a new axiom for bargaining solutions, named Proportional Concession Monotonicity (PCM), which imposes that no player benefits when all players collectively make proportional concessions with respect to their respective utopia values. We reconsider the leximin solution (Imai, 1983), and obtain an alternative characterization on the basis of PCM.
Gesehen am 29.11.2018
Available online 29 October 2011